PENGARUH LOKASI DAN MOTIVASI WISATA TERHADAP KEPUTUSAN BERKUNJUNG DI ALAM CURUG GONGSENG KUNINGAN JAWA BARAT - Rudhi Achmadi; Gys Dominggos Joshua Nendissa (LPPM and Travel Operation Department Universitas Asa Indonesia, 2018)
As we know that the decision of tourists to decide to visit a tourist attraction is influenced by many factors. Two of them are location and visiting motivation. Thus the manager of tourist attraction needs to pay close attention to these two factors to increase the number of tourist visits to the tourist attractions they manage. This study aims to determine the effect of location and tourist motivation on tourists to make decision to visit Curug Gongseng, Kuningan West Java. The research analysis was carried out using multiple linear regression. The result of the study indicated that simultaneously location variables and tourist motivation influence the visiting decision. Location variable and tourist motivation contribute 22.7% on tourist decision to do a visit